1972
DOI: 10.1071/ar9720753
|View full text |Cite
|
Sign up to set email alerts
|

Single-plant characters as a measure of field plot performance of wheat cultivars

Abstract: The 49 cultivars in the Fifth International Spring Wheat Yield Nursery (ISWYN) were grown as single plants in pots and 16 characters measured. Grain yield of the cultivars as single plants was not significantly correlated with ISWYN mean grain yields, although there were high correlations between single-plant and field performance in days to ear emergence, height, and 100-grain weight. ISWYN cultivar mean yields were used as the dependent variable in a stepwise regression analysis with the 16 single-plant char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 4 publications
1
20
0
4
Order By: Relevance
“…Further research is necessary to estimate this correlation. Syme (1972) and Fischer & Kertesz (1976) working with spring wheat (Triticum aestivum) concluded from their data that the harvest index of spaced plants offers a better criterion for improving grain yield under dense stands than grain yield itself or yield components. Our study, however, found harvest index to be a poor criterion for improving grain yield ( Table 4).…”
Section: Traitmentioning
confidence: 99%
“…Further research is necessary to estimate this correlation. Syme (1972) and Fischer & Kertesz (1976) working with spring wheat (Triticum aestivum) concluded from their data that the harvest index of spaced plants offers a better criterion for improving grain yield under dense stands than grain yield itself or yield components. Our study, however, found harvest index to be a poor criterion for improving grain yield ( Table 4).…”
Section: Traitmentioning
confidence: 99%
“…While, Syme (1972) and Fischer and Kertesz (1976) reported a close relationship of resource allocation to the grains with yield potential.…”
Section: Morphological Charactersmentioning
confidence: 99%
“…Numerous studies by plant breeders, using both forage species (e.g., Lazenby, 1957;Knight, 1960;Copeman and Swift, 1966) and crop species (e.g., Syme., 1972;Fischer and Kertez, 1976), have shown that only weak correlations exist between the yield of genotypes or populations as spaced-plants and their yield in dense monocultures. Few such comparisons have been made in the context of the ecological genetics of plant species, and the effects of competition on attributes other than yield have received little attention, though Caradus and Snaydon (1986) have compared populations of T repens for a number of morphological and physiological attributes in a diversity of conditions; they found widely different correlations, depending on the particular attributes and conditions considered.…”
Section: The Spaced-plant Trial Techniquementioning
confidence: 99%
“…The main exception to this is that plant breeders have made many comparisons of the performance of genotypes and populations as spacedplants and in dense stands (e.g., Lazenby, 1957 and 1965; Knight, 1960;Copeman and Swift, 1966;Syme, 1972;Fischer and Kertez, 1976). …”
Section: Introductionmentioning
confidence: 99%